Soft Storey Effects on Plastic Hinge Propagation of Moment Resisting Reinforced Concrete Building Subjected to Ranau Earthquake - Chee, Ghuan Tan; Wei, Ting Chia; Taksiah, A. Majid; Fadzli, Mohamed Nazri; M. I., Adiyanto (American Institute of Physics, 2017)
On 5th June 2015, a moderate earthquake with Mw 5.9 hit Ranau, resulted in damages of the existing nonseismically designed buildings, such that 61 buildings, including mosques, schools, hospitals and Ranau police headquarters were suffered from different level structural damages. Soft storey irregularity is one of the main reasons of the building damage. This study is to investigate the soft-story effect on the propagation path of plastic hinges RC building under seismic excitation. The plastic hinges formation and seismic performance of five moment resisting RC frames with different infill configurations are studied. The seismic performance of building is evaluated by Incremental Dynamic Analysis (IDA). Open ground soft storey structure shows the lowest seismic resistance, collapses at 0.55g pga. The maximum interstorey drift ratio (IDRmax) in soft storey buildings ranging from 0.53% to 2.96% which are far greater than bare frame ranging from 0.095% to 0.69%. The presence of infill walls creates stiffer upper stories causing moments concentrate at the soft storey, resulting the path of plastic hinge propagation is dominant at the soft storey columns. Hence, the buildings with soft storey are very susceptible under earthquake load.